Pinochet meets Polanyi? The Curious Case of the Chilean Embrace of "Free" Market Economics - Cypher, Jame M. (Journal of Economic Issues, 2004)
This article argues, within the context of Karl Polanyi's work, that the common view of Chile is doubly miscontrued, in terms of free market economics. Events since the end of the dictatorship (1989) tend to confirm Polanyi's hypothesis in 'The Great Transformation' (1957; discussed in the following section) while at the same time negating the Chicago School's view that a free market society could be built–even under a dictatorship. In Chile from September 1973 onward through 1989, the Chicago School–inspired economists known as the Chicago Boys, engaged in what would appear to be the most determined utopian endeavor of economic liberalism to set up a self-regulating market system. It is the hypothesis of this paper that the Chicago School failed spectacularly in this effort and that the credit they have widely received for successfully remaking the Chilean economy properly belongs to the antithesis of the Chicago School–successful state-led efforts to restructure the economy and foster development. Far from the fictitious utopia of the free market, under the dictatorship the state was also heavily involved in projects designed to massively transfer economic rents to the private sector. Consistent with Polanyi's thesis, the Chicago School was able to drastically reduce Chile's social legislation, labor legislation, and social controls over the exploitation of the natural resources of Chile only within the context of a military dictatorship. While Chile's elected governments have embraced the Chicago School's faith in unlimited and unregulated free international trade, in the area of social legislation and labor legislation there are very strong indications that civil society is systematically and effectively striving to overcome the retrograde steps imposed by the dictatorship.
Economics
Keywords: Chicago school of economics; Chile; economic conditions; economics; free enterprise; politics and government